Evaluación de la aplicación web de la universidad técnica de cotopaxi mediante el método empírico de la ingeniería de usabilidad para la optimización de su entorno con la carrera de ingeniería en sistemas, ubicada en la provincia de Cotopaxi, cantón Latacunga en el periodo académico 2013-2014 - Basantes Ortega, Cristian Jesús (2015)
This thesis aims to determine the degree of usability that owns the website of the Technical University of Cotopaxi through usability engineering, this allowed us to recommend changes or modifications according to data from the usability test applied to users of the site web. The methodology used for data analysis methodology using the technique of field survey questionnaire with the instrument. Analysis and interpretation of the results of the survey of teachers and students studying Computer Engineering and Computer Systems is important to know whether the level of usability is the website of the institution was made….